Ketogenic HMG‐CoA lyase and its product β‐hydroxybutyrate promote pancreatic cancer progression. (21st March 2022) - Gouirand, Victoire; Gicquel, Tristan; Lien, Evan C; Jaune‐Pons, Emilie; Da Costa, Quentin; Finetti, Pascal; Metay, Elodie; Duluc, Camille; Mayers, Jared R; Audebert, Stephane; Camoin, Luc; Borge, Laurence; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDA) tumor cells are deprived of oxygen and nutrients and therefore must adapt their metabolism to ensure proliferation. In some physiological states, cells rely on ketone bodies to satisfy their metabolic needs, especially during nutrient stress. Here, we show that PDA cells can activate ketone body metabolism and that β‐hydroxybutyrate (βOHB) is an alternative cell‐intrinsic or systemic fuel that can promote PDA growth and progression. PDA cells activate enzymes required for ketogenesis, utilizing various nutrients as carbon sources for ketone body formation. By assessing metabolic gene expression from spontaneously arising PDA tumors in mice, we find HMG‐CoA lyase (HMGCL), involved in ketogenesis, to be among the most deregulated metabolic enzymes in PDA compared to normal pancreas. In vitro depletion of HMGCL impedes migration, tumor cell invasiveness, and anchorage‐independent tumor sphere compaction. Moreover, disrupting HMGCL drastically decreases PDA tumor growth in vivo, while βOHB stimulates metastatic dissemination to the liver. These findings suggest that βOHB increases PDA aggressiveness and identify HMGCL and ketogenesis as metabolic targets for limiting PDA progression. Synopsis: The molecular mechanisms underlying metabolic flexibility of solid tumor cells exposed to oxygen deprivation remain poorly understood. This study identifies the ketogenic enzyme HMG‐CoA lyase (HMGCL) and its derivative β‐hydroxybutyrate (βOHB) as essential drivers of pancreatic cancer, highlighting ketone body metabolism as a regulatory nexus in metastasis. Systemic βOHB is metabolized by pancreatic adenocarcinoma (PDA) cells, fueling the TCA cycle. HMGCL and βOHB promote PDA tumor aggressiveness and metastatic dissemination. Ketone body metabolic enzymes are upregulated in PDA. PDA cells de novo generate ketone bodies from various carbon sources. Depletion of HMGCL limits oncogenic properties of pancreatic tumor cells in vivo, which is rescued by exogenous βOHB. Abstract : Systemic and cell‐intrinsic ketone body metabolism supports pancreatic cancer metastasis.